Antipredator function of vigilance re-examined: vigilant birds delay escape. (October 2019) - Tätte, Kunter; Ibáñez-Álamo, Juan Diego; Markó, Gábor; Mänd, Raivo; Møller, Anders Pape
Abstract : Vigilance is considered an effective antipredator behaviour in animals, and hence it should reflect fearfulness. While numerous aspects of vigilance have been extensively studied, there is a paucity of evidence regarding the role of vigilance in escaping from predators. In a multispecies approach, we measured vigilance (as the proportion of time spent in a head-up posture) and three consecutive components of escape behaviour, predetection distance, assessment interval and flight initiation distance, of wild birds in urban and rural habitats in three European countries. Escape behaviour was induced by a human observer walking towards the focal bird whose vigilance was measured beforehand. More vigilant individuals did not detect predators earlier than less vigilant ones. In addition, more vigilant individuals spent more time on risk assessment and escaped later. Body mass was positively correlated with vigilance for birds on higher perches, where we expected vigilance to be less important. Finally, urban birds were more vigilant than rural birds, suggesting that distractions in urban habitats might have a more profound impact on vigilance than the expected lower predation risk. These results challenge the underlying assumption that more vigilant individuals have a higher perceived risk of predation and hence better odds at avoiding predation. We explain our results in the context that higher levels of vigilance compensate for environmental distractions and for innate deficiencies or lack of experience that constrain the detection of predators. We suggest that a re-examination of the basic functions and markers of vigilance is needed before using it as a measure of fearfulness in birds. Highlights: Vigilant individuals did not become alert earlier than less vigilant individuals. Vigilant individuals assessed risk longer and escaped later. Urban birds were more vigilant than rural birds but escaped later. Vigilance increased with body mass for birds on higher perches.